EFL STUDENTS’ PERCEPTIONS ON THE INTEGRATION OF WHATSAPP IN A LOW-TECH LEARNING ENVIRONMENT - Novalita Fransisca Tungka; Olviani Cipta Ningsi Tarinje (Jurnal Bahasa Lingua Scientia, 2021)
This paper explores how WhatsApp as social media is embedded into the educational practices of university students. The paper draws on an analysis of 79 questionnaires and 10 online interviews. The questionnaire survey was administered online and collected from students majoring in English Education at Universitas Sintuwu Maroso, Poso, Sulawesi Tengah. The survey was followed up by online interviews, which were meant to provide deeper understanding of the students’ experiences on the integration of WhatsApp to aid their learning practices. The discussion in this paper focuses on how students make meaning of WhatsApp integration in their formal study. The results indicate that although WhatsApp has the potential as a space for learning, the students simply valued WhatsApp as a channel for exchanging information of the courses and other practical information. Based on these results, some models of social media integration in educational practices are suggested to be applied in the context of low-tech environment.